Phytochemical screening and in vivo and in vitro evaluation antioxidant capacity of Fargaria ananassa, Prunus armeniaca and Prunus persica fruits growing in Algeria - Saoudi, Soulef; Khennouf, Seddik; Mayouf, Nozha; Amira, Smain; Dahamna, Saliha; Hosni, Karim (Progress in Nutrition, 2020)
Purpose: Fruits are important source of phytochemicals such as polyphenols, flavonoїds, tannins, cartenoides and vitamins which poss antioxidant activity. The aim of this study is the screening of polyphenols and the evaluation of antioxidant activity in vitro and in vivo of Fargaria ananassa, Prunus armeniaca and Prunus persica (Rosacea family) fruits extracts. Methods: The antioxidant activity of hydromethanolic extracts were estimated by methods of the scavenging activity against DPPH, ABTS, hydroxyl radicals (HO.), β-carotene/linoleic acid model system, lipid peroxidation, reducing power and chelating activity. Total phenolics and flavonoids content in these extracts were determined using Folin–Ciocalteu’s reagent and Aluminum chloride colorimetric methods respectively. In vivo antioxidant activity was conducted by biological study using male wistar rats. Result: The results showed that Fargaria ananassa contains high amount of polyphenols and flavonoids (310 ± 0.003μg gallic acid /mg extract and 14.78 ± 0.001μg quercetin equivalent/mg extract respectively ), followed by Prunus armeniaca and Prunus persica, but the highest levels of tannin were found in Prunus armeniaca (127.9±0.003 μg tannic acid equivalent/ mg extract). Fargaria extract have a high antiradical effect towards DPPH radical, however, Prunus persica have a good effect in the inhibition of lipid peroxidation. The administrations of Fargaria extract (200 mg/kg and 600 mg/kg) elevates the plasma antioxidant activity and reduced the level of MDA with 85.07 ± 2.06% and 39.54 ± 1.11% respectively and increased the levels of GSH in the liver of rats. The UPLC analysis of extracts demonstrated the presence of various phenolic acids (gallic acid, cinnamic acid and hydrocinnamic acid) and flavonoids (rutin and flavons3-ols) in all extracts. Conclusion: These results support the idea that the consumption of fruits can reduce the risk of disease related to free radicals such as cancer, cardiovascular diseases, hypertension, diabetes and stroke. This effect can be attributed at least in part to the antioxidant properties of polyphenols present in the extracts.